Fungal Communities of Eucalyptus grandis Leaves Are Influenced by the Insect Pest Leptocybe invasa - Messal, Mandy; Vivas, María; Kemler, Martin; Begerow, Dominik; Brachmann, Andreas; Witfeld, Frederick; Naidoo, Sanushka; Slippers, Bernard (Frontiers in Microbiology, 2022)
Fungal communities in above-ground tree tissues are hyperdiverse and are influenced by biotic interactions with other organisms living in or on these tissues. These biotic interactions are, however, still poorly understood. In this study, we aimed to understand how insect-associated gall formation on Eucalyptus foliage correlates with the diversity of foliar fungal communities in surrounding healthy leaf tissue, as well as the co-occurrence patterns amongst the members of the fungal community. We used ITS metabarcoding to characterise the foliar fungal communities of 179 individual E. grandis trees. These trees were correlated with infestation levels of the wasp Leptocybe invasa (Eulophidae: Hymenoptera), which causes gall formation on shoot tips and leaves of its host. Fungal community networks were calculated using a Pearson correlation coefficient. The composition and diversity of fungal communities were influenced by the severity of L. invasa infestations. We identified potential Eucalyptus pathogens with high sequence abundance at all disease severity levels, but network analysis indicated that the co-occurrence of potential pathogens between no to mild and medium to heavy infestation differed significantly. A better understanding of microbial interactions, especially the role of pathogens, can be useful for controlling disease- and beneficial host-associated microbial communities.